1997
DOI: 10.1001/jama.1997.03550240047032
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ring Block, Dorsal Penile Nerve Block, and Topical Anesthesia for Neonatal Circumcision

Abstract: The most effective anesthetic is the ring block; EMLA is the least effective. It is our recommendation that an anesthetic should be administered to newborns prior to undergoing circumcision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…[16] reported that the SCRB had an unacceptable failure rate when compared with the subpubic penile block, most authors agree that the SCRB is an effective and safe anesthetic technique. [171819] Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…[16] reported that the SCRB had an unacceptable failure rate when compared with the subpubic penile block, most authors agree that the SCRB is an effective and safe anesthetic technique. [171819] Our results are consistent with these findings.…”
Section: Discussionsupporting
confidence: 92%
“…Compared to a dorsal penile root block or eutectic mixture of local anesthetics (EMLA) cream, the ring block has been shown to be the most effective means of pain relief for circumcision. 89 …”
Section: Local Anestheticsmentioning
confidence: 99%
“…[5] However, although the analgesic effect of EMLA is enough for removing the adhesions and for the placement of the clamp, it is not sufficient for serious pain arising from removal of the foreskin. The most common side effect of EMLA is methemoglobinemia which may develop due to the metabolism of prilocaine.…”
Section: Neonatal Circumcision Techniquesmentioning
confidence: 99%